A disciplina de história no Paraná: os compêndios de história e a história ensinada (1876-1905) - Toledo, Maria Aparecida Leopoldino Tursi (2006)
The present study investigates History as a school subject in the state of Parana. In order to keep track of the birth and development of the subject, a historical research was conducted based on debates about school education during the time when Parana had its status changed from 5th Judicial District of São Paulo to an independent Province. The selected bibliography led the investigation to the State School of Parana. The school was founded in 1846, by São Paulo State Law n. 33, under the name of Liceu de Curitiba, initially, an institution of high school education. It was only in 1858, though, after Parana was already a Province, that the school was effectively recognized as an institution of regular education, with proper locality. Also, 1858 was the year when History and Geography were created as school subjects at the Liceu. However, due to lack of students enrolled in History classes, the subject could not be legitimized at the time. In fact, the only subjects offered were French, Latin and Mathematics, until 1869, when the school was closed and the teachers and students were then transferred to a subventionary school, Nossa Senhora da Luz. During the subvention period, which lasted a year, there was still a lack of students to attend History classes. Actually, effective records of the subject being taught date back to 1876, when Liceu de Curitiba definitely stopped existing, and the Preparatory Institute and the Normal School (for teacher development at secondary level) were created. Because this event marked the History of Education in Parana in a significant way, this study examined the course of the above mentioned institution from its creation in 1876 until 1905. Thus, the focus is on how the school subject (History) appears in relation to the objectives of secondary education during the transition period from the imperial society to the Brazilian republic, during its creation and the long process prior to becoming a school subject at the Preparatory Institute and the Normal School (with the Republic advent this institution was further named Parana Gymnasium high education from 5th to 8th grades and Normal School). Therefore, understanding the objectives that defined History as a school subject in the state of Parana, which happened from 1876 to 1905, was the ultimate aim of the present research.